Floristic composition of Aksaz Wetland (Sinop) - BANİ, Barış; ELMAS, Emire (Biological Diversity and Conservation, 2022)
Aksaz wetland is located in Akliman district which is away from 10 km North of the city center of Sinop province. This study was performed between 2015 and 2017. 1274 plant samples were collected from the research area and all of them were identified. 444 specific and infraspecific taxa in 269 genera belonging to 71 families were determined. Among them one taxon belongs to Pteridophyts, two of them are Gymnosperms, and 441 out of 444 taxa are from Angiosperms. Additionally, the endemism ratio in the study area is 0.68% with three endemic species.
Keywords: 15. Life on land